2022
DOI: 10.1002/er.8198
|View full text |Cite
|
Sign up to set email alerts
|

Improved kinetics of reduction of alkaline water on the g‐CN‐ supported transition metal oxide/boride hetero‐interface: A case study

Abstract: Summary The presence of multiple active sites and hetero‐junction on a multi‐component hetero‐structured catalyst would exhibit modest hydrogen binding strength and charge transfer, as well as redistribution during interaction with the intermediates during the water reduction process. In this study, we synthesized a ternary iron oxide/nickel boride/graphitic carbon nitride (Fe3O4/NixB/g‐CN) composite as the electrode material for the reduction of water under alkaline environment. Preformed NixB seed and Fe3O4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 79 publications
(153 reference statements)
0
8
0
Order By: Relevance
“…The total XPS spectrum (Figure c) showed a significant increase in the content of oxygen and boron on the sample’s surface. From the B 1s spectrum (Figure d), B–B and Ti–B bonds disappeared from the sample’s surface after high-temperature oxidation, and only the B–O bonds (191–194 eV) , existed with high peak intensity. It indicates that the B powder and TiB 2 on the sample’s surface were entirely oxidized, and abundant B 2 O 3 was generated.…”
Section: Resultsmentioning
confidence: 99%
“…The total XPS spectrum (Figure c) showed a significant increase in the content of oxygen and boron on the sample’s surface. From the B 1s spectrum (Figure d), B–B and Ti–B bonds disappeared from the sample’s surface after high-temperature oxidation, and only the B–O bonds (191–194 eV) , existed with high peak intensity. It indicates that the B powder and TiB 2 on the sample’s surface were entirely oxidized, and abundant B 2 O 3 was generated.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the variation of current densities at definite overpotential showed that CoMo provided a higher current with the progress of reaction compared to others (Figure S6). The kinetics of the progressing reaction as well as the rate-determining step is reflected by the Tafel slope value, which is defined as the potential need to increase 10 units of current density . Generally, the HER proceeds through an adsorption step (Volmer step: H 2 O + Cat + e – → Cat–H + OH – and Tafel slope = 120 mV dec –1 ) followed by the desorption step, where the desorption step can be of two types: atom ion reaction (Heyrovskey reaction: Cat–H + H + + e – → H 2 + Cat + OH – , Tafel slope = 30 mV dec –1 ) and combination reaction (Tafel reaction: Cat–H + Cat–H → H 2 + 2Cat, Tafel slope = 40 mV dec –1 ).…”
Section: Resultsmentioning
confidence: 99%
“…OER involves the four-step adsorption/desorption process involving OH*, O* and OOH* intermediates, where the rate-determining step can be assumed from the electron-transfer coefficient (α) that signifies the lowering of free energy barrier through modification of the electrode–electrolyte interface potential. This α value can be calculated from the Tafel slope value following the relation: b = 2.303 R T F α , α = n normalf γ + n normalr β , where n f and n r are the numbers of electrons transferred before and each occurrence of RDS, respectively; γ is the stoichiometric number, typically 1, and β is the symmetrical potential barrier. , Now, the higher b values indicated that the adsorption step would be the slowest step during OER and the desorption would occur via proton hopping over the M–O interface. The progress of the reaction has further been understood from the post-OER XRD patterns of TMMos (Figure S7C–F), where the TMMo signed a weak odd ‘l’ reflection leading to a shift in the peak values showing that the cation–oxygen interaction has occurred strongly to which the Mo sites were distorted, although no structural changes were observed making it stable after the reaction as well and indicating Mo to be the active site for OER.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations